How many real roots does the equation
x
x
=
(
x
)
x
have?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Why x=0 is not a solution? I know that 0^ 0 is indeterminate, but always 0^0=0^0.
Log in to reply
Not quite! Indeterminate forms are not equal, even if they look exactly the same; that is, if 0 0 = 0 0 , then it would imply 0 0 − 0 0 = 0 , which is false since 0 0 − 0 0 is indeterminate.
Log in to reply
Why is 0 0 − 0 0 indeterminate? 0 0 equals infinity, and logically, infinity minus infinity equals zero, doesn't it?
Log in to reply
@Jehad Aly – Infinity minus infinity doesn't equal 0. Because you could double the first infinity and get 2inf-inf=inf-inf=0, but 2inf-inf=inf+(inf-inf)=inf+0=inf, thus 0=inf. That's why inf-inf is also an indeterminate form.
I'd argue that 0 0 = 0 0 1 , then we cannot determine its result
Actually, 0 0 is undefined.
Log in to reply
Some people use different definitions to describe indeterminate and undefined, but the most common definition that I've seen at a university level is that indeterminate refers to a form that can have several reasonable values. 0 0 , for example, could sensibly be 0 or 1 based on the two most obvious approaches: 0 x = 0 , x ∈ R + , and x 0 = 1 , x ∈ R − { 0 } . By the definition above, it is then indeterminate.
Log in to reply
@Caleb Townsend – But zero doesn't have an inverse, so that first one should be 0 x = 0 , x ∈ R + .
And the reason it is undefined at the "university level" is because they use the definition a x : = e x l n a , so 0 0 would be e 0 l n 0 , which is undefined because zero doesn't have a natural log.
It's nothing to do with indeterminate forms, which only apply to limits.
Log in to reply
@Whitney Clark – If a x is defined as e x ln a , how come 0 x = 0 for positive x ? ;)
Log in to reply
@Otto Bretscher – That's a good question. All I know is, zero squared or cubed is zero, the square root and cube root of zero is zero, and so on.
@Whitney Clark – ln 0 gives negative infinity, and multiplying an infinity of any sign with a 0 gives the indeterminate form in limits.
Log in to reply
@Paul Paul – I wasn't talking about limits, just plain exponentiation.
Log in to reply
@Whitney Clark – Whenever I say the result is infinite, then restricting myself to normal reals obviously means that it becomes meaningless.
@Caleb Townsend – There are limits where 0 0 could get anything.
In algebra 0 0 means 1 . So in this point of view 0 is a solution. It is a matter of convention we use. For istance N is considered as the set of all positive (strictly) integers by someone, and the set of all non negative integers by other. Wheter 0 belongs to N or not depends on our assumption...
Log in to reply
In any commutative unit ring ( R , + , ⋅ ) anyone can define by recursion, for every a ∈ R
a 0 = e m a n + 1 = a ⋅ a n for every poitive integer n
where e m is the neutral element for the operation ⋅ .
It is right that 1 is an obvious root.. But is there a mathematical way to get it?
Log in to reply
You can do it this way, Jehad: Take ln on both sides to find x ln x = x ln ( x ) = 2 x ln x , for x > 0 . Multiplying with x 2 , we find ( x − 2 ) ( ln x ) = 0 . The two solutions are x = 4 and x = 1 .
gud and simple
Taking natural logarithm from both sides yields:
x ln x = x ln x
⇔ ln x = 2 x ln x
⇔ ( x − 2 ) ln x = 0
⇔ ln x = 0 ∨ x = 2
⇔ x = 1 ∨ x = 4
Hence, there are two real roots.
Why don't you use log? is that okay to use log? what is the difference with use ln?
Log in to reply
That's the way I used to be taught - they're identical. I know it's only a naming convention, but somehow I find the notation ln more satisfying to the eye. Just a personal taste you know.
whenever i confuse i take log
x^(x^1/2) = x^(x/2)
x = 1 ............................................... (1)
or
x^1/2 = x/2
4x = x^2
x = 0 .................... refused
x = 4 .............................................(2)
This equation has only two real roots , 1 , 4
I found it easier to let x = y^2. We then get (y^2)^(sqareroot(y^2)) =( y^2)^y = y^2y on the left. On the right we get (squareroot(y^2))^(y^2) = y^(y^2). Thus, y^2y = y^(y^2), leaving 2y=y^2. When is this true? When y^2-2y = 0, or y(y-2)=0. Solving, y=0 or y=2, so x=y^2=0 or 4.
take log(base x) on both sides....you get: sqrt(x)=x/2 => x^2-4x=0 => x=0 or x=4
x=0 is invalid and you missed x=1 by taking log base x.
As,x to the power rootx = rootx to the power x; so, x to the power rootx = x to the power x/2; As the bases are same; rootx= x/2; Squaring both sides, x=x^2/4; x^2=4x; x^2-4x=0; x=0, x=4;
x^sqrt (x)={sqrt (x)}^x, as given... Raising both the sides by the power of sqrt (x)^(-1), we have, x={sqrt (x)}^sqrt (x). we get that only the values for x=1 & x=4 satisfy the equation.
Take log on either side and reduce the expression. (x^(1/2)) log x = x log(x^(1/2)) (x^(1/2)) log x = x (1/2) log x logx=0 or (x^(1/2)) = x (1/2) i.e. x=1 or x=4 Therefore 2 roots.
Problem Loading...
Note Loading...
Set Loading...
x = 1 is an obvious root.
The given equation can be re-written as x x = x 2 1 x . Equating the exponents we have x = 2 1 x or x ( x − 4 ) = 0 .
But 0 isn't a root of the original equation. Hence there are only two roots: 1 & 4